Pemaknaan Media Sosial Instagram dalam Membentuk Moralitas Remaja Muslim - Finan Azka Nuzilla Hilyah; Rizki Dwi Pangestu; Yayang Altifriani Afdha; Sultan Jody Akbar (Lisyabab : Jurnal Studi Islam dan Sosial, 2022)
This research was conducted to find out how Muslim teenagers interpret Instagram social media in shaping adolescent morality. Social media comes along with the development of technology. Every human job is made easier with the presence of very sophisticated hardware and software. However, technological developments do not always have a positive impact on mankind. The erosion of youth morals and morals often occurs and this cannot be separated from the influence of social media. Therefore, social media must be used wisely in order to help its users become better individuals. To find out the meaning of Instagram social media in shaping the morality of Muslim youth, this study uses a qualitative method with an interview approach. The resource persons in this study were two people with the criteria of Muslim youth and following Islamic accounts on Instagram social media. The results of this study indicate that adolescents interpret the media as a source of information. One of the information obtained is how a Muslim should act, behave, and speak. Social media Instagram is a secondary resource that helps teenagers improve themselves through Islamic content. The resource persons also shared this information with their colleagues so that they could also improve themselves. However, Islamic content on social media does not necessarily make teenagers want to change themselves. There needs to be awareness and willingness to improve themselves first, then social media, especially Instagram as a secondary source, can help someone improve themselves.